A digital platform for automated analysis of 1H NMR data: prototype framework of digital reference standard - Sunil Babu Paudel; Joo-Won Nam; Gonzalo R. Malca Garcia; Ben Shapiro; Pekka Laatikainen; Yang Liu (AAPS Open)
Abstract This study introduces an innovative approach to automatically analyzing 1H nuclear magnetic resonance (NMR) data, integrating a quantum mechanical spectral analysis (QMSA) to enhance efficiency over manual data analysis in NMR. This proposed digital platform features a standardized quantitative NMR (qNMR) procedure, digital Reference Spectra within a spectral library, and a visualized interactive interface for streamlined, automated NMR data analysis. This digital platform significantly reduces the need for manual intervention and shows promise in using spectral fitting to compare the calculated spectrum derived from a digital Reference Spectrum with an experimental spectrum. The digital platform excels in processing data of both single chemical and mixture, delivering accurate results, and positioning it as an essential tool for automatic 1H qNMR analyses. Case studies highlight the digital platform’s effectiveness, demonstrating its wide-ranging applicability. This shows that the proposed digital platform, based on a qNMR-based QMSA approach, offers reliable qualitative and quantitative analyses and paves the way for integrating digital reference standards into future compendial tests. Graphical Abstract